2009
DOI: 10.1098/rspb.2009.0947
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of muscle phenotype for extreme high altitude flight in the bar-headed goose

Abstract: Bar-headed geese migrate over the Himalayas at up to 9000 m elevation, but it is unclear how they sustain the high metabolic rates needed for flight in the severe hypoxia at these altitudes. To better understand the basis for this physiological feat, we compared the flight muscle phenotype of bar-headed geese with that of low altitude birds (barnacle geese, pink-footed geese, greylag geese and mallard ducks). Bar-headed goose muscle had a higher proportion of oxidative fibres. This increased muscle aerobic cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(147 citation statements)
references
References 35 publications
5
137
0
5
Order By: Relevance
“…Aside from the mechanism that enhances COX activity for oxygen use in Tibetan locusts living in hypoxic conditions, several other physiological mechanisms critical for oxygen supply have also been reported. For example, bar-headed geese have exhibited significant improvement through a series of cascading physiological steps of oxygen transport during hypoxia [15,33]. The genetic basis of the improved haemoglobin-oxygen affinity has been correlated with the substitutions in five exterior amino acid residues in high-altitude deer mice [34].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the mechanism that enhances COX activity for oxygen use in Tibetan locusts living in hypoxic conditions, several other physiological mechanisms critical for oxygen supply have also been reported. For example, bar-headed geese have exhibited significant improvement through a series of cascading physiological steps of oxygen transport during hypoxia [15,33]. The genetic basis of the improved haemoglobin-oxygen affinity has been correlated with the substitutions in five exterior amino acid residues in high-altitude deer mice [34].…”
Section: Discussionmentioning
confidence: 99%
“…1B) generate a space-filling alternative (Egginton & Ross, 1989 thereby allowing the exploration of the local influences associated with microvascular remodelling, as well as any mismatch between angiogenesis and local O 2 demand (Degens et al, 1992(Degens et al, , 2002(Degens et al, , 2006(Degens et al, , 2008Egginton et al, 2001;Wüst et al, 2009a). This gives Voronoi polygons an advantage in assessing the efficacy of applications to pathological scenarios, such as ischaemia, where potential therapeutic interventions include strength training (Deveci & Egginton, 2002;Suzuki et al, 2000), endurance exercise (Ahmed et al, 1997;Scott et al, 2009), electrical stimulation (Ebina et al, 2002), and alterations in muscle temperature (Egginton et al, 2001;Egginton, 2002). In addition to their ability to reproduce robust versions of the aforementioned global measures, Voronoi polygons have the capacity to provide indices of capillary supply to individual fibres, with both direct contact and indirect influence, and to fibres of different metabolic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Blier et al (2006) also found little evidence to suggest that functional differences in enzyme activity could explain the introgression of Arctic charr (Salvelinus alpinus) mtDNA into brook charr (S. fontinalis). Combining these types of approach with more sensitive techniques assaying mitochondrial function directly, such as respiration in isolated mitochondrial preparations (Scott et al 2009), will be valuable in determining whether introgressed mitochondria differ phenotypically from the native type and, ideally, how this might affect whole-animal fitness (reviewed by Dalziel et al 2009 andMelvin 2010). In this way, cases of mitochondrial introgression could potentially be used to link the effects of specific mtDNA mutations in introgressed genetic variants to phenotypic differences (Dalziel et al 2009;Scott et al 2011).…”
Section: Untangling Processes Driving Discordance From Biogeographic mentioning
confidence: 99%